Color Image and Video Enhancement - Celebi, Emre; Lecca, Michela; Smolka, Bogdan (Springer International Publishing : Imprint: Springer, 2015)
This text covers state-of-the-art color image and video enhancement techniques. The book examines the multivariate nature of color image/video data as it pertains to contrast enhancement, color correction (equalization, harmonization, normalization, balancing, constancy, etc.), noise removal and smoothing. This book also discusses color and contrast enhancement in vision sensors and applications of image and video enhancement.   ·         Focuses on enhancement of color images/video ·         Addresses algorithms for enhancing color images and video ·         Presents coverage on super resolution, restoration, in painting, and colorization.